The impact of US-China strategic competition on the idea of space as a “global commons” - Freeman, Carla P. (Frontiers in Space Technologies, 2025)
This article examines how US-China’s strategic competition is transforming the conceptualization of outer space as a “global commons.” While the global commons framework for space governance emerged from Cold War-era agreements emphasizing universal access, freedom of exploration and non-appropriation of outer space, contemporary geopolitical rivalry has fundamentally altered how the world’s leading space powers interpret and apply this concept. The analysis traces the historical evolution of space as a global commons from the 1967 Outer Space Treaty through recent policy shifts by Beijing and Washington. The research documents a striking reversal: the United States, once a champion of characterizing space as a global commons, rejected this characterization in 2020. Conversely, China, which once rejected global commons terminology, now uses it to describe outer space. These competing approaches are crystallizing in rival lunar development programs, with the US-led Artemis initiative confronting the China-Russia International Lunar Research Station. The findings demonstrate how great power rivalry has upended the traditional normative frameworks countries have used to determine their policy for space.